Orisinalitas Pneumatologi John Calvin sebagai “Teolog Roh Kudus” - Herman Herman; Ceria Ceria; Fredy Simanjuntak (DIEGESIS: Jurnal Teologi Kharismatika, 2022)
John Calvin is one of the foremost theologians among reformed theologians. His works are a major contribution to the history of Protestant development even to the present day. But along the way, the development of Protestant theology has produced two views on the sustainability of the gifts of the Spirit. One of the views is to see that the gifts of the Holy Spirit no longer occur after the Biblical canonization (cessationism). This view is dominated by most Calvinist theologians and eventually creates the stigma that Calvin theology does not emphasize the Holy Spirit in its doctrines, even though in his day Calvin was given the nickname "The Theologian of the Holy Spirit”. This fact goes against the built stigma. To answer this question, the writer uses the descriptive-qualitative research method by reviewing the theology of the Holy Spirit written by Calvin in his masterpiece Institutes of The Christians, and the context at that time. In the end, this research finds that the main points of the Calvin’s Holy Spirit theology that are not indicated to the built stigma about Calvin’s Holy Spirit theology are the basis of cessationist or rationalist， but on the contrary, in accordance to the nickname given to him as the theologian of the Holy Spirit who integrated the theology of the Holy Spirit in all of his doctrines and ministries based on the Bible. AbstrakJohn Calvin merupakan salah satu teolog terkemuka dari kalangan teolog-teolog reformasi. Karya-karyanya memberikan kontribusi besar dalam sejarah perkembangan Protestan hingga saat kini. Namun dalam perjalanan perkembangan teologi Protestan telah menghasilkan dua pandangan mengenai keberlangsungan karunia-karunia Roh. Salah satunya melihat bahwa karunia-karunia Roh Kudus tidak lagi berlangsung setelah pengkanonan Alkitab (cessasionism), pandangan ini didominasi oleh sebagian besar teolog Calvinis dan akhirnya menimbulkan stigma bahwa teologi Calvin tidak menekankan Roh Kudus dalam doktrin-doktrinnya. Padahal pada zamannya Calvin diberi julukan “Teolog Roh Kudus”. Kenyataan ini menimbulkan kontradiksi dengan stigma yang terbangun. Untuk menjawab pertanyaan ini maka penulis menggunakan metode penelitian kualitatif deskriptif dengan meninjau kembali teologi Roh Kudus Calvin yang tertulis dalam maha karyanya yaitu Intitutes of The Christian dan konteks pada masa itu. Pada akhirnya penelitian ini menemukan pokok-pokok teologi Roh Kudus Calvin yang tidak terindikasi kepada stigma yang terbangun mengenai teologi Roh Kudus Calvin adalah dasar cessasionist atau rasionalis tetapi justru sebaliknya seperti julukan yang diberikan kepadanya sebagai teolog Roh Kudus yang mengintegrasi teologi Roh Kudus dalam semua doktrin dan pelayanannya dengan dasar Alkitab.